An Experimental Study on Drilling of Glass Fiber Reinforced Plastic - Sharma, Vikas (My University, 2010)
Delamination is recognized as one of the most critical defects that can result from the machining of composites. Delamination is a major problem associated with drilling fiber-reinforced composite materials that, in addition to reducing the structural integrity of the material, also results in poor assembly tolerance and has the potential for long-term performance deterioration. Delamination due to drilling has been a major research for many years and a considerable amount of work has been done to reduce it. This thesis work has involved the determination of different factors affecting the hole quality and cause of delamination in a glass fiber reinforced plastic. The various process parameters like different twist drill bits of different point angle and different materials have been taken. The thrust forces and torque were measured for different machining conditions. The piezoelectric dynamometer has been used for measuring thrust forces and torque on varying the feed rate, speed, point angle and drill materials. The different materials of drill bit has been used like Tungsten carbide, High speed steel and M50(high speed steel) The optimum value has been determined with the help of main effect plot and ANOVA Tables to findout which parameter has affected most for increasing thrust force and torque. The mathematical modeling has been carried out sing Minitab 15 software and different models has been analysed with help of the taguchi design using orthogonal array. The Universal microscope has been used which determines delaminated diameter in GFRP specimens. The finite element method has been done by applied using Ansys11.0 software which helped to find out delaminated diameter with different control factors like point angle, drill material etc. The failure criteria has been applied in ansys software for finding delamination occurring glass fiber composite around the drilled holes.
M.E. (CAD/CAM and Robotics)
Keywords: drilling,fem,plastics